Do Titanium Mini-Implants Have the Same Quality of Finishing and Degree of Contamination before and after Different Manipulations? An In Vitro Study - Tatiana Zogheib; André Walter-Solana; Fernando de la Iglesia; Eduardo Espinar; Javier Gil; Andreu Puigdollers (Metals, 2021)
Evaluate the quality of finishing and degree of contamination before and after handling and surface treatment of titanium (Ti) orthodontic mini-implants (OMIs). A scanning electron microscope (SEM) study on ninety-six titanium OMIs was done. Energy-Dispersive X-ray Analysis (EDX) identified the present particles on manufactured OMIs surfaces. Then, OMIs were manipulated with gauze (dry sterile, soaked in chlorhexidine) and gloves (latex, nitrile) to evaluate the contamination of these handling materials. Finally, OMIs underwent surface treatments and were placed in bone to observe the contaminants they released. Roughness (Ra) and wettability with contact angle parameter (CA) were measured on these treated OMIs. Machined OMIs presented surface irregularities and were contaminated with manufacturing-process particles (carbon, plastic Polyvinyl Chloride PVC, aluminum). Hand-manipulated OMIs were also contaminated by the handling materials. OMIs surface characteristics were as follows: acid-etched (Ra ≈ 1.3 μm, CA ≈ 66°), machined (Ra ≈ 0.3 μm, CA ≈ 68°), SB (Ra ≈ 3.3 μm, CA ≈ 78°), and SBAO (Ra ≈ 3.1 μm, CA ≈ 92°). Bone was contaminated by OMIs surface defects and extra particles. Manufactured OMIs have surface contaminants that increase with clinical handling. Surface treatments (SBAO, a combination of sandblasting and anodic oxidation) increase the roughness and contact angle, which play an important role in osseointegration. Surface-treated OMIs leave titanium particles in the bone during their insertion-removal. The use of a gauze soaked in chlorhexidine is recommended when handling OMIs. Further investigations would be interesting to study more variables and confirm the present results.